Bank Air Susu Ibu dalam Perspektif Hukum Islam - Dwi Condro Wulan (Lex Renaissance, 2022)
Breast milk is the most perfect nourishment that is clean and contains lots of nutrients for babies because the processing is carried out naturally in the mother's body. When a mother is unable to breastfeed for various reasons, breast milk can be obtained from breast milk donors. This fact prompted European scientists to come up with the idea of establishing a breast milk bank which aims to help mothers who cannot breastfeed their babies directly. The purpose of this study is to identify and analyze the breast milk bank in the perspective of Islamic law and Islamic foundations that allow breast milk bank. This study uses the theory of legal certainty and the theory of benefits. The research method in this study uses a juridical approach. The results of this study conclude that first, the basis for the permissibility of breast milk bank is the opinion of Al-Imam asy-Syafi'i who asserted that, "Breastfeeding is not unlawful except for five separate feedings." This means that the source of breastfeeding that leads to breastfed siblings is the baby suckling directly to the mother's or donor's breast, while the milk obtained from the breast milk bank is obtained from several different mothers or even mixed and breastfeeding is given to the baby using a special spoon, bottle or tube. The breast milk bank aims to make it easier for babies to get breast milk whose mothers cannot give breast milk to their babies for certain reasons, especially for babies who are born prematurely because premature babies are required to be given breast milk instead of formula milk. Second, breastfeeding is very important for babies because it contains nutrients that are needed for optimal growth and development, for the health and survival of babies. Yusuf Al-Qardhawi stated that he did not find any reason to prohibit the establishment of a breast milk bank as long as it aims to realize solid syar'iyah benefits and to meet the needs that must be met, then it is permissible to establish a breast milk bank. Key Words: breast milk, breast milk bank, breast milk donor, health law, Islamic law AbstrakASI (Air Susu Ibu) merupakan makanan yang paling sempurna, bersih serta mengadung banyak nutrisi bagi bayi karena pengolahannya dilakukan secara alami dalam tubuh ibu. Saat seorang ibu tidak dapat memberi ASI karena berbagai sebab, maka ASI bisa didapat dari pendonor ASI. Fakta tersebut mendorong Ilmuwan Eropa memunculkan gagasan untuk mendirikan bank ASI yang tidak lain bertujuan untuk membantu para ibu yang tidak bisa menyusui bayinya secara langsung. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis bank ASI dalam perspektif hukum Islam dan landasan Islam memperbolehkan bank ASI. Penelitian ini menggunakan teori kepastian hukum dan teori kemanfaatan. Metode penelitian pada penelitian ini menggunakan pendekatan yuridis. Hasil penelitian ini menyimpulkan pertama, yang menjadi landasan diperbolehkannya bank ASI adalah pendapat Al-Imam asy-Syafi‘i yang berkata, “Penyusuan tidaklah menyebabkan keharaman kecuali lima kali susuan yang terpisah.” Artinya sumber penyusuan yang menyebabkan sepersusuan itu adalah bayi menyusu langsung ke payudara ibu atau pendonor, sedangkan ASI yang didapat dari Bank ASI didapatkan dari beberapa ibu yang berbeda atau bahkan dicampur dan pemberian ASI kepada bayi menggunakan sendok, botol maupun tabung khusus. Bank ASI bertujuan untuk mempermudah bayi mendapatkan ASI yang ibunya tidak dapat memberikan ASI kepada bayinya karena alasan tertentu terutama bagi bayi yang lahir prematur karena bayi prematur diharuskan diberi ASI bukan susu formula. Kedua, pemberian ASI sangat penting diberikan kepada bayi karena kandungan nutrisi yang sangat dibutuhkan untuk tumbuh kembang yang optimal, untuk kesehatan dan kelangsungan hidup bayi. Yusuf Al-Qardhawi menyatakan bahwa ia tidak menemukan alasan untuk melarang pendirian bank ASI asalkan bertujuan untuk mewujudkan maslahat syar'iyah yang kokoh dan untuk memenuhi kebutuhan yang harus dipenuhi, maka boleh untuk mendirikan bank ASI. Kata-kata Kunci: ASI; bank ASI; donor ASI; hukum kesehatan; hukum Islam